THE EFFECT OF DIFFERENT PACKAGING MATERIALS ON QUALITY SEAWEED SWEETS (Eucheuma cottonii) DURING STORAGE AT ROOM TEMPERATURE - Ria S, Imay Christina; Sari, Ira; ', Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The study was intended to examine the effect of different packaging materials on quality of seaweed sweets during room temperature storage. About 250 g seaweed which was taken from a fish market in Pekanbaru was prepared for seaweed sweets with addition of 125 g palm sugar and 20 g cinnamon. The sweets was packaged in 3 different types of packaging materials, HDPE, LDPE, PP and stored for 14 days at room temperature. The product were evaluated for sensory quality, moisture, reducing sugar, and fungi every 0, 7 and 14 days. The results indicate that the seaweed sweets packed with HDPE had the best quality during storage and its quality was still acceptable up to the end of a storage. Moisture and reducing sugar of the seaweed sweets were 31,57%, 44,79% respectively. The species of fungi found on the product was Aspergillus sp.Keywords : Seaweed, sweets, palm sugar, cinnamon, moisture, reducing sugar, packaging, fungi